Integration Of The Values Of Amanah And Maqashid Syariah In The Efficiency Of Statistical Data Collection - Anisah Nisa; Fauzani; Nafiza Julia; Siti Rasada; Tassa Tassa (Indonesian Journal of Islamic Economics and Business, 2026)
This study was motivated by issues surrounding the effectiveness and efficiency of data collection methods at the Central Statistics Agency (BPS), which are key to providing accurate data for national economic planning. Differences in infrastructure and human resource readiness often cause imbalances between manual PAPI (Paper and Pencil Interviewing) and digital CAPI (Computer Assisted Personal Interviewing) methods. This study aims to analyze the comparison between the two modes by integrating the values of trustworthiness and the principles of maqashid sharia. The approach used is descriptive qualitative with data collection techniques through in-depth interviews with employees and field officers of the BPS in Sarolangun Regency. The results of the study show that the use of CAPI improves speed, accuracy, and cost efficiency compared to PAPI, although it still faces technical obstacles such as internet connectivity and staff adaptation. PAPI remains relevant in areas with limited digital infrastructure. These findings emphasize the importance of training, technological readiness, and the integration of trustworthiness in maintaining data quality. In conclusion, the combination of these two modes is considered the most effective in supporting statistical surveys in the regions while reflecting the application of Islamic economic values in efficient, transparent, and public welfare-oriented public data management.